Votes and violence: Electoral vote share and international conflict in democratic states. (November 2021) - Haynes, Kyle
This article argues that the effect of a democratic leader's electoral margin of victory on their conflict behaviour once in office is highly dependent upon the state's institutional structure. I show that, uniquely in parliamentary democracies, governments that win a larger share of the vote are significantly less likely to initiate disputes abroad. Such governments entail broad coalitions that, combined with the ever-present possibility of governmental collapse and new elections, require leaders to pursue a more cautious, lowest-common-denominator foreign policy. This effect is significantly stronger for right-wing governments. Conversely, in presidential democracies, I find that electoral vote share has no effect on a leader's subsequent conflict propensity. Vote shares thus function very differently in parliamentary and presidential systems, with important implications for conflict behaviour abroad.